TANGGAPAN KONSUMEN TERHADAP PAKET WISATA DI CV. BILAVA TOUR RIAU PEKANBARU - Annisa, Fitri; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
One product that is in a travel agency is a tour package. In a tour that is carried out, consumers certainly expect the tour package that has been promised according to the what is in the field. This study aims to determine consumers response to tour package at CV. Bilava Tour Riau Pekanbaru. To find out the consumers response to tour package can be measured through 5 components, which are :Tourist Attractions, Events, Transportation, Accommodation, and Meals&Drinks. The research will be measured and known by quantitative methods. This study took 100 people as the samples or respondents by using the Slovin adequacy formula. The technique of data collection in this study uses observasion, questionnaires and documentation. This study usesÂ  the theory of Etta Mamang Sanadji & Sopiah,2010, named the Likert Scale to measure the interval in the quantitative data. Based on the results, the study indicates that consumer responses to the implementation of tour package at CV. Bilava Tour Riau Pekanbaru is in the Very Good category, and it scores 6.413.Â keywords : Consumer Response, Tour Package, Travel Agent